Resveratrol Protects Caenorhabditis elegans from Ultraviolet B-induced Photoaging via skn-1 - Siswanto, Ferbian Milas (Molecular and Cellular Biomedical Sciences, 2025)
Background: Resveratrol (RSV) is a polyphenol with potent antioxidant activity and is abundant in fruits. There has been a lot of scientific evidence regarding the anti-aging effect of RSV. Aging can be induced by UV-B (photoaging) due to the production of reactive oxygen species (ROS) and oxidative stress. This study aimed to test the anti-photoaging activity of RSV on UV-B -induced Caenorhabditis elegans.Materials and methods: C. elegans was cultured at 20˚C in nematode growth medium (NGM) and was subjected to various concentrations of RSV and UV-B. The UV-B light exposure was given on day 0 post-synchronization at a dose of 100 J/m2 using a UV cross-linker. The health span (indicated by pharyngeal pumping rate) and lifespan of worms were observed. The quantification of collagen was performed using a Sircol Collagen assay kit. The mRNA expression level of gcs-1, col-19, hus-1, cep-1, egl-1, and ced-13 was examined by qRT-PCR. Results: UV-B reduced pharyngeal pumping rate, shortened the lifespan, decreased collagen, and increased the expression of apoptosis-related genes (hus-1, cep-1, egl-1, and ced-13). RSV ameliorated these aging phenotypes induced by UV-B. Anti-aging activities of RSV were not observed in the skn-1 loss-of-function strain (VC1772, skn-1(ok2315)), indicating the critical involvement of skn-1 in the mechanism of action of RSV. The activation of skn-1 was shown by elevated skn-1 target gene that play role in glutathione biosynthesis called gcs-1.Conclusion: RSV prevents accelerated aging due to UV-B in C. elegans by enforcing skn-1 signaling pathway and its downstream gcs-1 gene expression.   Keywords: anti-aging, resveratrol, oxidative stress, UV-B